Air-blast response of sacrificial cladding using low density foams: Experimental and analytical approach. (August 2017) - Ousji, H.; Belkassem, B.; Louar, M.A.; Reymen, B.; Martino, J.; Lecompte, D.; Pyl, L.; Vantomme, J.
Highlights: The study of the efficiency of sacrificial claddings using polyurethane (PU) as crushable core to mitigate a blast load. The analytical model of Hanssen over-estimates the front plate displacement and hence, the minimum polyurethane thickness. The fluid-structure interaction (FSI) effect cannot be neglected in the case of low density foam. The Kambouchev–Noels–Radovitzky (KNR) theory is suitable to simulate the FSI effect in the case of low density foam. Graphical abstract: Abstract: The present paper focuses on the study of the fluid-structure interaction (FSI) and the mitigation effect of sacrificial cladding using polyurethane (PU) as crushable core material under blast loading. A small-scale test set-up is developed for that purpose. An explosive driven shock tube (EDST) is used to generate a uniformly distributed blast load. The sacrificial cladding is composed of the PU and a metal front plate. The effects of the PU properties (plateau stress and thickness) and front plate mass are investigated; three PU densities are used: 30, 35 and 50  kg/m 3 ; four front plate masses are considered: 86, 147, 339 and 497  g. Depending on the loading rate, the transmitted plateau stress to a rigid structure is increased by 10 to 50 % of the plateau stress measured in a quasi-static test. The reflected impulse that is measured on a rigid and fixed boundary is now reduced by 4 to 12%, due to the front plate motion. Hence, considerable FSI effect is observed. Among several models, the theory proposed by Kambouchev, Noels and Radovitzky (KNR) in combination with the Hanssen analytical model allow a better prediction of the sacrificial cladding response. Due to the low density (high mass ratio 9 < M front plate / Mfoam < 51) and the low plateau stress, the impulse reduction can be estimated by considering that the front plate moves as a free-standing plate. An adapted-Hanssen model for low density foam, predicting the enhancement/attenuation limit, is proposed.